Revision of the Hoplodrina implacata group (Lepidoptera: Noctuidae: Noctuinae: Caradrinini) of Taiwan, with descriptions of four new species - Wu, Shipher; Owada, Mamoru (Zootaxa, 2018)
The noctuid taxon Hoplodrina implacata species complex comprises so far five species ranging in China, Japan, Korea and Taiwan. Previously only H. implacata (Wileman & West, 1929) was recorded in Taiwan. The present study reviews this group in Taiwan, totally four new species, i.e., H. cienensis sp. nov., H. obscura sp. nov., H. bunun sp. nov., H. kononenkoi sp. nov, are described and a key to all Taiwanese species is given.